Dihedral F-Tilings of the Sphere by Equilateral and Scalene Triangles - II - Breda, A. M. d’Azevedo; Ribeiro, Patrícia S.; Santos, Altino F. (The Electronic Journal of Combinatorics, 2008)
The study of dihedral f-tilings of the Euclidean sphere S^2 by triangles and r-sided regular polygons was initiated in 2004 where the case r=4 was considered [5]. In a subsequent paper [1], the study of all spherical f-tilings by triangles and r-sided regular polygons, for any r5, was described. Later on, in [3], the classification of all f-tilings of S^2 whose prototiles are an equilateral triangle and an isosceles triangle is obtained. The algebraic and combinatorial description of spherical f-tilings by equilateral triangles and scalene triangles of angles β, γ and δ (β>γ>δ) whose edge adjacency is performed by the side opposite to β was done in [4]. In this paper we extend these results considering the edge adjacency performed by the side opposite to δ.